Long-term survival in extensive-stage small-cell lung cancer treated with different immune checkpoint inhibitors in multiple-line therapies: A case report and literature review - Zhang, Xu; Zheng, Jiabin; Niu, Yun; Xue, Chongxiang; Yu, Yixuan; Tan, Kexin; Cui, Huijuan (Frontiers in Immunology, 2022)
Background: Extensive-stage small cell lung cancer (ES-SCLC) is highly malignant, highly prone to recurrence, and has a short survival period, and it is very difficult to achieve long-term survival, which has not been significantly improved in the last 20 years. For a long time, platinum-based chemotherapy has occupied the core position in the treatment of small cell lung cancer (SCLC), but there are few options for treatment drugs or regimens, and if disease progression occurs, the options for follow-up regimens are obviously limited. The advent of immunotherapy has changed this situation to some extent, and immunotherapy has shown some effect in improving efficiency and prolonging survival, whether in first or third-line therapy, but it is still unsatisfactory. Case presentation: A 59-year-old patient with ES-SCLC experienced disease progression after four lines of treatment including synchronous radiotherapy, chemotherapy and anti-angiogenesis. However, the patient still benefited when switching to the programmed cell death receptor-1 (PD-1) inhibitor toripalimab in combination with chemotherapy in the fifth line; even after the development of immune resistance, the patient still benefited after switching to tislelizumab in combination with different chemotherapy regimens or alone in the sixth and seventh lines; and following the progression of tislelizumab in combination with chemotherapy, the patient again profited after switching to durvalumab in combination with anlotinib, and again achieved a progressive-free survival (PFS) of 11 months. Overall, the patient achieved a total of 45 months of PFS and 50 months of overall survival, with a shocking and exciting 30 months of PFS achieved in the immune combination phase alone. Conclusion: We report a patient with ES-SCLC who achieved long-term survival after at least eight lines of therapy including chemotherapy, anti-angiogenesis, and different immune checkpoint inhibitors (ICIs). This suggests that long-term survival in SCLC is possible with aggressive, combined, and standardized treatment. Otherwise, immunotherapy postline enablement can still benefit patients, rechallenge after immune resistance is also possible in SCLC, and combination with chemotherapy or anti-angiogenic therapy can improve the efficacy and prolong survival. This will provide new ideas and options for the selection of treatment options for SCLC.